DINAMIKA COPING STRES ORANGTUA DALAM MENDAMPINGI ANAK BELAJAR DARI RUMAH: STUDI KUALITATIF PASCA PANDEMI - Ika Suarsi (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2025)
This study aims to describe the coping strategies of parental stress in assisting children to study from home after the Covid-19 pandemic. The method used is a descriptive qualitative approach with data collection techniques through structured interviews with a number of parents in several districts in South Sulawesi who have had the experience of assisting children during learning from home. The data analysis technique uses thematic analysis. The results of the study show that parents who assist their children to study from home use more problem-focused coping, but there are also some who use emotional-focused coping. The implications of this study emphasize the importance of stress management that focuses on solving problems so as to help parents in their children's learning process at home. Keyword : parental stress, coping stress, stress